Micro Business Performance in DKI Jakarta: Analysis of the Influence of Financial Management and Digital Marketing with Islamic Business Ethics as a Moderating Variable - Fathul Muslimin, Nanda; Nurasyiah, Aas; Azizah Al-Adawiyah, Rumaisah (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in Indonesia's economic growth. However, there are still many MSMEs that have difficulty advancing to class, as evidenced by the number of micro-businesses that dominate. Apart from that, many micro-businesses still have difficulty adopting digital and accessing capital. This research analyses Financial Management and digital marketing with Islamic business ethics as a moderating variable influencing micro-businesses performance in DKI Jakarta. This research was carried out using the Resource Based View (RBV) model approach. Data were analyzed using the SEM-PLS method with SmartPLS version 3 software. The research results show that the level of Financial Management, digital marketing, Islamic business ethics, and business performance is in the high category. Other findings show that the level of Financial Management does not affect business performance. Islamic business ethics can moderate the influence of Financial Management and digital marketing on the performance of micro-businesses in DKI Jakarta. This research implies that digital marketing and Islamic business ethics play an important role in improving the performance of micro-businesses. At the same time, Financial Management requires Islamic business ethics as moderation to have a significant impact on the performance of micro-businesses in DKI Jakarta.